2010
DOI: 10.1186/1475-2875-9-265
|View full text |Cite
|
Sign up to set email alerts
|

A method of active case detection to target reservoirs of asymptomatic malaria and gametocyte carriers in a rural area in Southern Province, Zambia

Abstract: Background Asymptomatic reservoirs of malaria parasites are common yet are difficult to detect, posing a problem for malaria control. If control programmes focus on mosquito control and treatment of symptomatic individuals only, malaria can quickly resurge if interventions are scaled back. Foci of parasite populations must be identified and treated. Therefore, an active case detection system that facilitates detection of asymptomatic parasitaemia and gametocyte carriers was developed and tested in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 19 publications
7
105
2
2
Order By: Relevance
“…To our knowledge, this investigation presents the first genetic data directly linking parasites causing asymptomatic infections among household members with those causing symptomatic disease. Similar to prior studies 1923 , we previously noted that CC in this cohort were 2.5 times more likely to have RDT+ household members than were control children 2 indicating household-level hotspots of high-risk individuals. Herein, we extended this association using our parasite genotyping approach to quantify the degree of genetic similarity between infected individuals.…”
Section: Discussionsupporting
confidence: 87%
“…To our knowledge, this investigation presents the first genetic data directly linking parasites causing asymptomatic infections among household members with those causing symptomatic disease. Similar to prior studies 1923 , we previously noted that CC in this cohort were 2.5 times more likely to have RDT+ household members than were control children 2 indicating household-level hotspots of high-risk individuals. Herein, we extended this association using our parasite genotyping approach to quantify the degree of genetic similarity between infected individuals.…”
Section: Discussionsupporting
confidence: 87%
“…26 Studies conducted in Zambia, Senegal, and Swaziland found that the number of tested individuals to identify one infected individual ranged from 37 to 250. 11,12,27 In our study area, a mean of 90 RDTnegative residents were tested for each RDT-positive individual identified and a mean of 66 qPCR-negative residents were tested for each qPCR-positive, RDT-negative individual identified. A mean of 24 qPCR-negative residents of index case households were tested for each qPCR-positive, RDTnegative individual identified within an index case household.…”
Section: Discussionmentioning
confidence: 99%
“…However, because microscopy requires extensive training, quality materials, and several years of experience to attain and maintain proficiency, routine diagnosis by microscopy is of variable quality, and lower‐density infections are frequently not identified. Nucleic acid‐based tests (NATs) have consistently demonstrated superiority to RDTs and microscopy in detecting infections at levels below the detection limits of a competent microscopist [29–34]. As countries progress towards malaria elimination, the need to detect submicroscopic infections is becoming increasingly important, as reservoirs of infected persons may sustain transmission even without this manifesting in clinical illness.…”
Section: Alternatives For Malaria Diagnosismentioning
confidence: 99%